Предмет: Алгебра,
автор: oleg1999vk
(-a-3)x+6x+4a=0 решить относительно x
Ответы
Автор ответа:
0
- Х * ( A + 3 ) + 6X = - 4A
- XA - 3X + 6X = - 4A
-XA + 3X = - 4A
- X * ( A + 3) = - 4A
- X = - 4A / ( A + 3)
X = 4A / ( A + 3 )
- XA - 3X + 6X = - 4A
-XA + 3X = - 4A
- X * ( A + 3) = - 4A
- X = - 4A / ( A + 3)
X = 4A / ( A + 3 )
Похожие вопросы
Предмет: Окружающий мир,
автор: 89061711308alex
Предмет: История,
автор: valyanss
Предмет: Химия,
автор: Аноним
Предмет: Алгебра,
автор: nepogodinaanna
Предмет: Право,
автор: timurmahmutov